Temporal Change and Effects of Perfluoroalkyl Substanses (PFASs) on Thyroid Hormone Levels in Mother-Cub Pairs of Polar Bear (Ursus maritimus) from Svalbard in 1998 and 2008 - Nilsen, Else Mari Espseth (Institutt for biologi, 2011)
High levels of persistent organic pollutants (POPs) have been detected in the Arctic wildlife. While many of the traditional POPs have been reported to decline the last decades, emerging contaminants such as perfluoroalkyl substanses (PFASs) have been detected in increasing amounts in biota worldwide. PFOS has been the major PFASs detected and the leading manufacturer of PFOS announced a voluntarily phase-out of the perfluorooctanesulfonyl fluoride (POSF) chemistry and ended the production in 2002. However, other PFASs are still being used in the industry and no regulations have been established. The toxicological effects of PFASs are not fully elucidated, but they have been linked to hepatotoxicity, developmental toxicity, immunotoxicity and disruption of hormone homeostasis.The aim of this study was to investigate temporal changes of PFASs and to evaluate possible relationships between PFASs and circulating thyroid hormone (TH) levels in polar bear (Ursus maritimus) mother-cub pairs from Svalbard sampled in 1998 (12 mother-cub pairs) and 2008 (9 mother-cub pairs). Plasma samples from all polar bears were extracted by liquid-liquid extraction (LLE) using methanol and analysed for perfluorobutanoic acid (PFBA), perfluoropentanoic acid (PFPeA), perfluorohexanoic acid (PFHxA), perfluoroheptanoic acid (PFHpA), perfluorooctanoic acid (PFOA), perfluorononanoic acid (PFNA), perfluorodecanoic acid (PFDA), perfluoroundecanoic acid (PFUnDA), perfluorododecanoic acid (PFDoDA), perfluorotridecanoic acid (PFTrDA), perfluorotetradecanoic acid (PFTrDA), perfluorobutane sulfonate (PFBS), perfluorohexane sulfonate (PFHxS), perfluorooctane sulfonate (PFOS) and perfluorooctane sulfonamide (PFOSA) using liquid chromatography mass spectrometry (LC-MS). Total thyroxine (TT4), free thyroxine (FT4), total triiodothyronine (TT3) and free triiodothyronine (FT3) were quantified by the use of radioimmunoassay (RIA). Relationships between PFASs, THs, age (only mothers), capture day and biometric variables were investigated by the use of ...